Impact of aluminosilicate additives on potassium retention during biomass combustion - Nichols, David (2020)
The slagging and fouling characteristics of biomass fuels can act as a barrier to their use as a fuel for thermal power generation. Biomasses with high alkali metal and alkaline earth metal contents, in particular those with high potassium contents, have high slagging and fouling propensities due to the formation of low melting temperature mineral phases. Under slow heating conditions using a muffle furnace, olive cake ashes have been produced at low temperature to retain inorganic volatile compounds while fully oxidizing carbon. These ashes have subsequently been heated with and without kaolin additives in different ratios to high temperatures, under both slow and fast heating rate conditions, in a muffle furnace and drop tube furnace respectively. Particular focus has been on the interactions of olive cake and kaolin in drop tube furnace combustion at temperatures ranging between 1000-1450°C and in 10% O2 – conditions representative of pulverized fuel combustion. Two additive ratio test series were conducted involving additive ratios ranging from 20% kaolin in olive cake ash (equivalent to 2% additive in raw fuel) to 50% kaolin in olive cake ash (equivalent to 10% additive in raw fuel). These tests were conducted at two temperatures: 1150°C and 1300°C. It was found that as the additive ratio increased, a threshold level for retention of volatile potassium was approached for each temperature. At 1150°C this value was 100% while at 1300°C this threshold level was approximately 80%. Furthermore, log curves were produced from the results obtained. These approximations serve to offer an insight into the levels of retention that might be achieved as a function of additive ratio. Notably, it would appear that high levels of retention are attainable with small additive ratios at the optimum temperature of 1150°C. From these additive ratio experiments it can clearly be seen that the combustion temperature has a significant effect on the efficacy of the kaolin additive. To further investigate this, an experimental test series was conducted involving DTF testing with 50% kaolin in olive cake ash at 1000°C and 1450°C. It was found that the level of retention at 1000°C was similar to that found at 1300°C (approximately 70%) while at 1450°C, 40% retention was measured. It is expected that at 1000°C the reaction is not under thermodynamic control and so the reduced retention is due to the slower kinetics at that temperature. This is not the case at the two higher temperatures of 1300°C and 1450°C. At these very high temperatures it is possible that there may be some degradation of the kaolinite additive which reduces its ability to react with the potassium. Following the experiments with olive cake and kaolin, some further tests were conducted with miscanthus and wood as alternative feedstocks with different levels of potassium. While these tests were limited in number, they did show significant signs of substantial retention of volatile potassium. With wood in particular being a favoured feedstock in large scale biomass combustion (in part due it its low ash content) further research in this area is expected. Additionally, the use of an alternative aluminosilicate additive was explored. The additive chosen was coal fly ash due to its high availability and low cost. When compared with the results achieved with kaolin, the coal fly ash that was used performed poorly. The notable contrast between the fly ash and the kaolin additive was a much lower alumina to silica ratio. When considering the ternery mineral phase diagram for the system K-Al-Si and the area of high melting temperature phases that exist where higher ratios of alumina are present, it is expected that the alumina to silica ratio of the additive is key to its performance. To further investigate this, further coal fly ash additives comprising of higher alumina to silica ratios should be tested. The use of Mineral Liberation Analysis in this research afforded the opportunity to examine the form of potassium species (by association) present in olive cake ash samples. By using this method, it was observed that the volatile potassium present in the starting fuel existed primarily as KOH. By comparing this starting material with the ash following combustion with and without kaolin at 1150°C and 1300°C, it was possible to see the transformations that occur to the potassium species. In the absence of the additive it was found that while all KOH was volatilised and lost, some of this volatile potassium migrated to form potassium silicates. In the presence of the additive however, this migration did not occur. In preference, a large proportion (up to 100%) of the KOH reacted with the aluminosilicate additive to form potassium aluminium silicate mineral phases. Thermodynamic data available in literature demonstrates that this is due to the favourable ΔG energies of formation for this reaction. By further analysis of the molar ratios of elements present in the mineral phases detected, it was possible to speculate as to the identity of potential specific compounds in the ash samples. These include the most commonly reported products of the reaction of K with Al-Si: kalsilite and leucite. By using this method it was found that the reaction product kalsilite was most likely to exist in large quantities in the samples.